The role of social projects in reducing unemployment in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
To date, the concept of "project" and "social project" are widely used in discussions on social and economic development of the country as a whole. The project is coordinated execution of multiple, inter-related activities, and, thirdly slowness limited in time, with a defined beginning and end. Socially project - is designed by the proponent of social innovation, which aims to create, upgrade or maintenance of the changing environment of the material or spiritual values, which is the space - time and resource boundaries and whose impact on people deemed positive in their social value. Thus, the project of social work as a system formulated project objectives established for the purpose of social institutions, physical objects, social protection systems, developed and approved by the relevant dokumentov- programs, plans, calculations, estimates, calculation of the necessary resources (material, financial, labor, time), the complex management decisions, activities to achieve their goals.
Keywords: Рroject; social projects; unemployment; social program; social policy.